Gleicher Lohn für gleiche Arbeit am gleichen Ort? Die Entsendung von Arbeitnehmern in der Europäischen Union - Werner Eichhorst (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2005)
– Based on the example of the posting of workers in the construction industry, this paper examines what impact the opening up of the European Single Market for services has had on an industry that was protected in the past against international competition. It is shown how different institutional framework conditions in individual EU states lead to location competition also in the services sector. In a second step the study analyses how attempts have been made at European and national level to re-regulate the legislation applicable to posted workers. Starting out from a situation of legal uncertainty, countries with high labour costs attempted at national level to reduce the cost advantage of foreign producers by extending their respective minimum standards to cover posted workers. Diverging solutions emerge depending on the constellation of the political economy and on the institutional repertoire. These national regulations anticipated the effects of a Community law solution that was able to be adopted subsequently as a framework directive. It protects the national regulations legally without making substantial interventions. Whilst the European law regulation is 'gentle on the autonomy' in this sense, the national regulations on the posting of workers had to be 'acceptable to the Community'. Especially in Germany this led to modifications in the collective bargaining system in the construction industry. Finally the paper also shows that a regulation aimed at protecting an industry that is exposed to competition can not halt decline or structural change.
Keywords: 330; Arbeitnehmerentsendegesetz; Baugewerbe; ausländische Arbeitnehmer; EU-Binnenmarkt; Regulierung; Rechtsvereinheitlichung; EU-Osterweiterung - Auswirkungen; ökonomische Faktoren; internationaler Wettbewerb; internationale Zusammenarbeit; Lohnpolitik; Lohnhöhe; europäische Integration; Europäische Union